Guerre Civile, violences et mémoires : retour des victimes et des émotions collectives dans la société espagnole contemporaine - Maud Joly (Nuevo mundo - Mundos Nuevos, 2008)
Contemporary Spanish society is confronted with a formidable challenge: to manage, sixty years later, the coming out of a traumatic past; a past which has imprinted highly conflicting memories. Emanating from the civilians, the demand - to recognise and rehabilitate the victims/vanquished of the Civil War (1936-1939) and that of the dictatorship- engages in a re-evaluation of the memory of this sensitive community, namely that of the Republicans. This article proposes to analyse, on the one hand, the paradigmatic affirmation arising from the memory of republican women, memory recovered from amongst the memory of the vanquished of both the civil war and the dictatorship. On the other hand, it is a question of grasping the relationship between memories and territories, between the rekindling of differed mourning and the rites of the present. Finally the grasping of these singular dynamics involves reconsidering the tense rapport with a traumatic past, re-renderings and claims in the present and a certain replay of collective emotions.